PENGARUH DEAD ENDORSER TERHADAP BRAND PERSONALITY DAN DAMPAKNYA DALAM MENCIPTAKAN INTENSI PEMBELIAN KUKUBIMA ENER-G! - HAPPY ROHMANA (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
The aims of this research is to analyze the direct effect between dead endorser towards the brand personality and purchase intention, as well indirectly effect of dead endorser towards purchase intentions through brand personality. This research used samples as much 100 respondents who were in Kebomas-Gresik area and ever see ads of KukuBima Ener-G!. The analytical method used was path analysis. The analysis showed that the dead endorser has direct effect on brand personality, dead endorser has no direct effect on purchase intention, brand personality directly affects the purchase intention, and dead endorser has indirect effect on purchase intention through brand personality.